1975
DOI: 10.1021/es60111a013
|View full text |Cite
|
Sign up to set email alerts
|

Color removal by clays. Kinetic study of adsorption of cationic and anionic dyes

Abstract: Experiments were designed to study the kinetics of adsorption of two industrial dyes-methylene blue (cationic) and sulfur blue (anionic)-by kaolinite and montmorillonite clays. The cationic dye was removed from aqueous solution at a continuously decreasing rate from 10 mg/g min to 0.07 mg/g min by montmorillonite whereas kaolinite adsorbed the dye at a faster and uniform rate of 16 mg/g min. The anionic dye was removed at a uniform rate of 2.3 mg/g min by kaolinite and 2.6 mg/g min by montmorillonite. The appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…1. The adsorption processes of MB molecules occurring on each of the tested adsorbents reached equilibrium after 2 h. This result is in agreement with the investigation of Sethuraman and Raymahashay [19]. However, Zhao and Wang [20] reported that the equilibrium in adsorption of MB on bentonite, which consists mainly of montmorillonite, was reached within 3 h. Some workers described the adsorption process of MB on montmorillonite particles as divided into two parts [15,21]: rapid adsorption on the external surface of the clay by ion exchange and aggregation, followed by deaggregation of the MB dimer and the monomer migrating to the interlamellar position of the clay.…”
Section: Adsorption Equilibrium and Adsorbed Amountsupporting
confidence: 91%
“…1. The adsorption processes of MB molecules occurring on each of the tested adsorbents reached equilibrium after 2 h. This result is in agreement with the investigation of Sethuraman and Raymahashay [19]. However, Zhao and Wang [20] reported that the equilibrium in adsorption of MB on bentonite, which consists mainly of montmorillonite, was reached within 3 h. Some workers described the adsorption process of MB on montmorillonite particles as divided into two parts [15,21]: rapid adsorption on the external surface of the clay by ion exchange and aggregation, followed by deaggregation of the MB dimer and the monomer migrating to the interlamellar position of the clay.…”
Section: Adsorption Equilibrium and Adsorbed Amountsupporting
confidence: 91%
“…The clay minerals exhibit a high affinity for cationic dyes (Sethuraman, 1975). The adsorption takes place largely by the mechanism of cation exchange; exchangeable metallic cations are released from the clay mineral into the aqueous phase and organic cationic dye molecules are replaced (Sethuraman, 1975).…”
Section: Maximum Removal Amountmentioning
confidence: 99%
“…The adsorption takes place largely by the mechanism of cation exchange; exchangeable metallic cations are released from the clay mineral into the aqueous phase and organic cationic dye molecules are replaced (Sethuraman, 1975). The raw MtKhl was expected to remove the highest BB-41 amount, which was not the case, and the adsorption could occur only on surface.…”
Section: Maximum Removal Amountmentioning
confidence: 99%
“…The Ðrst, sharper, portion (the dashed) is the external surface adsorption stage19 or instantaneous adsorption stage. 21 The second, gradual linear, portion is the gradual adsorption stage21 and the third, linear, portion is the Ðnal equilibrium stage. 20,21 In this model, the chitosan Ñakes are treated as being surrounded by a boundary layer Ðlm through which the dyes must di †use prior to external adsorption on chitosan surface.…”
Section: Adsorption Dynamicsmentioning
confidence: 99%
“…21 The second, gradual linear, portion is the gradual adsorption stage21 and the third, linear, portion is the Ðnal equilibrium stage. 20,21 In this model, the chitosan Ñakes are treated as being surrounded by a boundary layer Ðlm through which the dyes must di †use prior to external adsorption on chitosan surface. The second sections of Figs 8 and 9, between about 10 and 40% dye adsorption are due to intraparticle di †usion being predominant in the ratecontrolling step.…”
Section: Adsorption Dynamicsmentioning
confidence: 99%